ACTR-69. FEASIBILITY STUDY OF THE EMULATE THERAPEUTICS™ VOYAGER SYSTEM IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA. (11th November 2019) - Barkhoudarian, Garni; Blondin, Nicholas; Chowdhary, Sajeel; Fonkem, Ekokobe; Vaillant, Brian; Kesari, Santosh
Abstract: BACKGROUND: The EMulate Therapeutics Voyager system is an investigational non-sterile, non-invasive, non-thermal, non-ionizing, portable, home-use medical device that uses a specific, localized ultra-low radio frequency energy ( ul RFE ® ) cognate for the treatment of brain cancer. METHODS: This open-label, multi-center study (NAT-109) enrolled adults newly diagnosed with GBM. Following surgical debulking, patients were enrolled and treated concurrently with temozolomide, radiotherapy, and Voyager. The objective of the study is to assess if the Voyager is a safe and feasible treatment for newly diagnosed GBM when combined with standard of care. The primary outcome measure is safety, assessed by the incidence and evaluation of any adverse events (AEs) associated with the Voyager. The secondary outcome measure is clinical utility, assessed by progression-free survival and overall survival. RESULTS: Enrollment is closed, and treatment and long-term follow-up is ongoing. A total of 37 patients were enrolled and treated. 27 patients reported 282 AEs, none of which required withdrawal from the study. One AE was reported as probably related to the device - i.e., mild dysesthesia, which resolved without interruption or cessation of treatment with the device. 15 patients reported 28 SAEs, and none were reported as related to the device. 56% of patients were progression-free at 6 months, and 43% were progression-free at 12 months. 89% of patients were still alive after 6 months, 71% were still alive after 12 months. CONCLUSIONS: The Voyager system appears to be safe and feasible for the treatment of newly diagnosed GBM. Given that therapy is delivered non-invasively and no device-related serious adverse events were reported, further prospective study of the investigational device is planned.